The Proposed Transformational Leadership Model in the 2010‘s for International Programs in Hospitality and Tourism - Thavornsuwanchai, Aimorn (Scholar: Human Sciences, 2015)
As we move rapidly into 21st century leaders face the challenge of being effective in a global knowledge environment. This research studies the factors of Transformational leadership model in 2010‘s is a leadership style that creates valuable and positive change in the economic crisis. Results on economic crisis around the world are impacting with every types of business, especially in the part of hotel and tourism in Thailand. The numbers of recruiting staffs were declining for hotels and tourism. This is a major problem for new graduates‘ because a few of them could find job that related with hotels and tourism. The researcher would like to find out some model that can help or support the leadership in the International Programs in Hospitality and tourism for Thai Higher education universities in Thailand. There are three aspects: 1) Propose the theory of transformational leadership, 2) Issues on Curriculum Development, 3) Effects on economic crisis and decreasing of employment. Within the range of these three aspects there are ten factors which will be focused in this study: transformation leadership development, curriculum development, leadership perception, universities conditions, leader‘s knowledge, ICT assisted teaching and learning, declining of economy, owner‘s perception, student‘s affair department, and quality assurance. The study is to investigate those ten factors for both public and private international universities. There are ten international universities in Thailand were randomly, and concerned only the master programs. Name of ten International University in Thailand: Assumption University, Silpakorn University, Mahidol University, Burapha University, Stamford University, Ramkhamhaeng University, Dusit Thani College, Naresuan University, Rangsit University, and Prince of Songkla University. All sample universities should have run in English language programs. The first part in the research design was identified all factors of transformational leadership, and leader‘s knowledge from various sources such as websites, journals, research, online data base, textbooks, and library. The second part of research design is interviewing: to gather information of owners‘ perception, student affairs department, and ICT teaching and learning by using open-ended questions. The results of this research, the researcher could find out new information that supported new model of transformational leadership for 2010‘s. Researcher is expected out from review of the literature, can be suggested that findings are as follows: The model of transformational leadership for 2010‘s, the model will be developed by our research is divided into seven sections: 1) Universities vision, 2) Organizational value, 3) Universities goals, 4) Characteristics of leadership, 5) Owners‘ perception, 6) Students‘ communities,7) Instructional support. As the results what can be happening to improve the effectiveness on the model of Transformational Leadership for 2010‘s for the Leaders of the International University in Thailand.